2011
DOI: 10.1007/4243_2011_26
|View full text |Cite
|
Sign up to set email alerts
|

One-Photon and Two-Photon Excitation of Fluorescent Proteins

Abstract: Fluorescent proteins (FPs) offer a wide palette of colors for imaging applications. One purpose of this chapter is to review the variety of FP spectral properties, with a focus on their structural basis. Fluorescence in FPs originates from the autocatalytically formed chromophore. Several studies exist on synthetic chromophore analogs in gas phase and in solution. Together with the X-ray structures of many FPs, these studies help to understand how excitation and emission energies are tuned by chromophore struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 119 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…After the discovery of GFP in the 1960s, and later the cloning of the gene, it has been shown that GFP can be expressed in other organisms and yet remain fluorescent. , Significant investment has been made into improving the photophysical properties of fluorescent proteins (FP) for their nonobtrusive use in real-time bioimaging. A great variety of fluorescent proteins have been synthesized and characterized, spanning a broad spectrum from blue to red fluorescent proteins. , The color of fluorescence is mainly controlled by the chromophore that is formed by three precursory residues. , By altering these amino acids, different maturation routes lead to different chromophore structures (many examples are mentioned in this work). In addition to the chromophore, the surrounding protein structure can also influence various photophysical properties of the protein .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the discovery of GFP in the 1960s, and later the cloning of the gene, it has been shown that GFP can be expressed in other organisms and yet remain fluorescent. , Significant investment has been made into improving the photophysical properties of fluorescent proteins (FP) for their nonobtrusive use in real-time bioimaging. A great variety of fluorescent proteins have been synthesized and characterized, spanning a broad spectrum from blue to red fluorescent proteins. , The color of fluorescence is mainly controlled by the chromophore that is formed by three precursory residues. , By altering these amino acids, different maturation routes lead to different chromophore structures (many examples are mentioned in this work). In addition to the chromophore, the surrounding protein structure can also influence various photophysical properties of the protein .…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of fluorescent proteins have been synthesized and characterized, spanning a broad spectrum from blue to red fluorescent proteins. 5,6 The color of fluorescence is mainly controlled by the chromophore that is formed by three precursory residues. 7,8 By altering these amino acids, different maturation routes lead to different chromophore structures (many examples are mentioned in this work).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A representation is provided in Figure . The different structure of the chromophore combined with a different local environment tune the spectroscopic properties of the three GFP variants. The chosen GFP variants span the broad variation of excitation energy of GFP-like fluorescent proteins containing the same 4-( p -hydroxybenzylidene)-5-imidazolinone chromophore in the anionic protonation state: mTFP and PhiYFP are among, respectively, the most blue-shifted and most red-shifted variants, while Dronpa is the intermediate between the two. The measured excitation energies of 2.74, 2.46, and 2.36 eV are experimentally observed for mTFP , Dronpa , and PhiYFP , respectively.…”
Section: Application To Gfpsmentioning
confidence: 99%
“…The main advantages of FPs are that, in contrast to synthetic organic fluorophores, they are produced by cells via gene transcription and translation, so that FPs can be expressed in distinct cell compartments, such as organelles and membranes. Comprehensive reviews of FPs' applications in biochemistry, as well as their structure tuning and the outline of anticipated future improvements are available elsewhere [133][134][135].…”
Section: Fluorescent Proteinsmentioning
confidence: 99%